Elucidation Of Genetic Variability, Heritability, Correlation And Path Coefficient In Carrot (Daucus Carota L.) (Applied Biological Research, 2023)
An experiment was conducted at the Punjab Agricultural University, Ludhiana,  India, for 2 years (2019-20 and 2020-21), to study the genetic variability,  heritability, correlation and path coefficient analysis in 28 genotypes of Asiatic  carrot under 8 environments. The experiment was laid out in RBD with three  replications. The analysis of variance showed that the genotype’s mean sum of squares was significant for all the traits studied, indicating that significant  variation existed among them. A wide range of variation existed for average root  length, root weight, root diameter, core diameter and root shoot ratio i.e., 14.5- 21.0 cm, 40.9-77.8 g, 2.2-2.7 cm, 0.93-1.56 cm and 0.86 to 1.29, respectively. The  average marketable yield of genotypes ranged between 365.55 to 584.55 q ha-1.  Vegetative traits like shoot length varied from 42.0-64.7 cm, shoot weight from  44.71-80.14 g, and the number of leaves from 5.4 -7.2 among all genotypes. The  magnitude of phenotypic coefficient of variation was greater than the  corresponding genotypic coefficient of variation for all the traits indicating that  trait expression is environmentally influenced. Root-shoot ratio, shoot length, number of leaves, root length, and root diameter all have exhibited highest  heritability and moderate genetic advance that suggested additive gene action.  Strong character association of root length, root diameter and root weight with  marketable yield suggested as selection criteria for higher yield.
Keywords: Correlation; Daucus carota; heritability; path analysis; variability